Value of animal fat and alfalfa hay in high-concentrate lamb rations - Menzies, C.S. (Kansas Agricultural Experiment Station, 2011)
In a previous test (Livestock Feeder’s Day Bulletin 473) adding 10% animal fat to a ration containing 45% alfalfa hay did not affect rate of gain but materially improved feed efficiency and lowered cost per unit gain. This test was conducted to determine the value of fat and additional hay in a high concentrate ration for lambs fed during the hot summer.
Keywords: Lamb; Animal Fat; Alfalfa hay; Feed efficiency